Ambiguous Prayers in 1 Timothy 2:1–2: A Postcolonial Reading - Jeong, Donghyun (Biblical interpretation, 2024)
This article examines the request for prayers ὑπὲρ βασιλέων in 1 Timothy 2:1–2 by focusing on three exegetical questions: (1) Who are the βασιλεῖς? (2) Are prayers for βασιλεῖς distinguishable from prayers to βασιλεῖς? And (3) to whom is this exhortation directed? The article argues that the rhetorical construction of this passage emulates and internalizes imperial ideology, but the very act of imitation has the potential to cause colonial anxiety by obscuring the colonial subjects behind this document and by disrupting any attempt at fixed interpretation.